2002
DOI: 10.1016/s0378-1097(02)00919-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of domains found within a lytic enzyme produced by Streptococcus equi subsp. zooepidemicus

Abstract: Zoocin A is a lysostaphin-like streptococcolytic enzyme produced by Streptococcus equi subsp. zooepidemicus 4881 that specifically targets the cell walls of some closely related species. On the basis of sequence homology it was suggested that zoocin A was a domainstructured enzyme with the N-terminal domain responsible for catalysis (CAT) and the C-terminal domain for target recognition (SBD). Polypeptides corresponding to zoocin A (rZooA) and each of the putative domains (rCAT and rSBD) were prepared by use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 19 publications
2
34
0
1
Order By: Relevance
“…Streptococcolytic activity of rZOO and Cd-rZOO was determined by use of a dye-release assay with Remazol brilliant blue-labeled, heat-killed cells of Streptococcus pyogenes FF22 as substrate as previously described [7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Streptococcolytic activity of rZOO and Cd-rZOO was determined by use of a dye-release assay with Remazol brilliant blue-labeled, heat-killed cells of Streptococcus pyogenes FF22 as substrate as previously described [7].…”
Section: Methodsmentioning
confidence: 99%
“…The protein is composed of two domains, an N-terminal catalytic domain (CAT) followed by a threonine-proline rich linker sequence, and then the target-recognition domain (TRD), which is responsible for specific recognition of cell wall architecture on sensitive strains [7]. Zoocin is a member of a superfamily of endopeptidases that selectively hydrolyze peptide cross bridges in peptidoglycans of the cell wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…zooepidemicus 4881 (Akesson et al 2007 ). It is composed of an N -terminal catalytic domain of putative endopeptidase activity and a C -terminal cell wall -binding domain (Lai et al 2002 ). It was shown that zoocin A -susceptible streptococcal species include, aside from S. equi , S. pyogenes , Streptococcus mutans , and S. gordonii .…”
Section: Other Bacteriocinsmentioning
confidence: 99%
“…Their action mechanism is different from those of other bacteriocins, in that they promote lysis of the cell wall of the target microorganism. Their Nterminal portion is homologous to an endopeptidase involved in cell wall synthesis, while the C-terminal portion is responsible for recognition of the target cell (Lai, Tran, & Simmonds, 2002).…”
Section: Class IIImentioning
confidence: 99%